INTERNALISASI NILAI JIWA BERDIKARI DALAM PANCA JIWA PESANTREN MELALUI KEGIATAN PENCAK SILAT DI PONDOK PESANTREN AR-RISALAH SLAHUNG PONOROGO - Masduqi, Fariz (Integrative Perspectives of Social and Science Journal, 2025)
Masduqi, Faris 2024. Internalizing the value of the spirit of independence in the five souls of Islamic Boarding Schools through Pencak Silat activities at Islamic Boarding Schools Ar-Risalah Slahung Ponorogo. Islamic Religious Education Research Program, Faculty of Islamic Religion, Muhammadiyah University, Ponorogo. Supervisor (I) Dr. Rido Kurnianto, M.Ag (II) Dr. Aldo Redho Syam, M.Pd The reason education is the main goal of a country is because education is considered a long-term investment aimed at growing the human qualities of the country's future. In order to improve the quality of education based on the importance of Islamic religious values, it is necessary to integrate religious material into the learning process through classroom teaching and other forms of external teaching in the form of student activity units. Looking back over the last few decades, several problems facing education in Indonesia today give rise to worrying paradigms. One factor is the neglect of values, especially Islamic religion, in the learning process. In contrast to this phenomenon, Pencak Silat as one of the non-academic activities in the Islamic boarding school environment hopes to help foster the spirit of independence of Ar-Risalah Slahung Ponorogo students. The purpose of this research is to (1) describe the implementation of the five souls concept which is internalized in the pencak silat ar-risalah slahung Ponorogo. (2) Describe the process of internalizing the five souls through pencak silat at Pondok Ar-Risalah Slahung. (3) Describe what is meant by internalizing the values ​​of an independent spirit at the Panca Jiwa Islamic Boarding School through the pencak silat activities of the Ar-Risalah Slahung Islamic Boarding School. Next, descriptive analysis is used to collect, aggregate, organize, summarize and analyze data, and its validity is checked through triangulation. The results of this research are: (1.) The concept of the five souls of independence internalized by Persita Pondok Ar-Risalah Slahung Ponorogo, there are 7 five souls of independence, namely: independence, tenacity, emotional independence, communication skills, determination and consistency, self-awareness and ability overcome difficulties. (2) At the Ar-Risalah Slahung Ponorogo Islamic Boarding School, the process of internalizing the five separate souls is carried out through appreciation of the knowledge, teachings and values ​​of the five souls which are utilized in various activities. achieved through routine training, promotion exams, competition between classes, and special training. (3.) Internalizing the values ​​of the spirit of independence into the meaning of the Panca Jiwa Islamic Boarding School through pencak silat activities at the Ar-Risalah Slahung Ponorogo Islamic Boarding School: Training students to become better individuals and inspiring them to become useful people for the nation. community and students. The formation of independent character can be a reference for developing educational projects at the Ar-Risalah Slahung Ponorogo Islamic Boarding School.